Food banking and emergency food aid: expanding the definition of local food environments and systems - Claire Thompson; Dianna Smith; Steven Cummins (BMC, 2019)
Abstract If current trends in food insecurity continue then the diets of low-income people may become characterised by the inclusion of significant amounts of donated and surplus food accessed via the third-sector. These developments have yet to be integrated into macro models and concepts of the food environment. Addressing this caveat is necessary in order to both help build an evidence base to challenge policies that exacerbate the drivers of food insecurity and to inform interventions aimed at improving the diets of disadvantaged populations.